Immunogenicity and safety of PRP-T conjugate vaccine given according to the British accelerated immunisation schedule. Issue 4 (April 1992) - Booy, R; Taylor, S A; Dobson, S R; Isaacs, D; Sleight, G; Aitken, S; Griffiths, H; Chapel, H; Mayon-White, R T; Macfarlane, J A
Abstract : The immunogenicity and safety of a new Haemophilus influenzae type b conjugate vaccine, PRP-T, was studied in 107 infants from the Oxford district. The vaccine was given concurrently with diphtheria, pertussis, tetanus, and polio vaccines at 2, 3, and 4 months of age. Symptoms after immunisation were recorded by a parent. Sera were obtained before the first immunisation and at 5 months of age and the antibodies were measured by both radioimmunoassay and enzyme linked immunosorbent assay (ELISA). No serious adverse reactions were observed and there was no increase in the incidence of expected minor side effects. By radioimmunoassay, the geometric mean titre of serum anticapsular antibody increased from 0.09 micrograms/ml before immunisation to 5.01 micrograms/ml after three immunisations. Ninety eight per cent of children had antibody concentrations consistent with protection (greater than or equal to 0.15 micrograms/ml). IgG antibody concentrations measured by ELISA correlated well with total antibody concentrations measured by radioimmunoassay (r = 0.864). These results provide encouragement that routine immunisation against H influenzae type b at 2, 3, and 4 months of age, could prevent most cases of disease in children in the UK.